Preventing SARS-CoV-2 In-Hospital Infections in Cardiovascular Patients and Medical Staff: An Observational Study From the German Heart Center Berlin - Schöppenthau, Doreen; Weiß, Karl Jakob; Estepa-Martinez, Misael; Hommel, Matthias; Miera, Oliver; Schoenrath, Felix; Hübler, Sabine; Obermeier, Martin; Pieske, Burkert; Stawowy, Philipp (Frontiers in Medicine, 2021)
Objective: COVID-19 is a highly contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Preventing in-hospital infections is crucial to protect patients and hospital staff. Methods: At the very beginning of the COVID-19 pandemic, the German Heart Center initiated obligatory wearing of surgical facemasks for patients and employees, SARS-CoV-2 screening for all patients and symptom-based testing for employees. In addition, access restriction, closure of outpatient departments and postponing non-urgent procedures were implemented with community-initiated regulations. Results: During the observation period (03/16/2020 – 04/27/2020) 1128 SARS-CoV-2 tests were performed in 983 persons (1.1 tests/person; 589 in patients and 394 in hospital employees). Up to 60% of the clinical work force were tested based on symptoms and risk (62.5% symptoms, 19.3% direct or indirect contact to known COVID-19, 4.5% returnee from risk area, 13.7% without specific reason). Patient testing for SARS-CoV-2 was obligatory (100% tested). The overall prevalence of positive tests during the observation period was 0.4% (n = 5 out of 1128 test performed). The incidence of new infections with SARS-CoV-2 was 0.5% (n =5 out of 983 individuals; 3 health care workers, 2 patients). No in-hospital infections linked to these cases occurred, despite a mean number of 14.8 in-hospital contacts. Conclusion: Comprehensive SARS-CoV-2 testing and surgical facemasks for patients and hospital staff, in addition to others measures, are key factors for the early detection of COVID-19 and to prevent spreading in the vulnerable hospital population.